Portadores nasofaríngeos de bacterias potencialmente patógenas en pre-escolares de Maracaibo (2000-2001) - Castellano-González M; Perozo-Mena A; Ginestre-Pérez M; Ávila-Roo Y (Universidad del Zulia,Facultad de Medicina,Departamento de Enfermedades Infecciosas y Tropicales, 2002)
Abstract: Frequently, the nasopharynx is colonized by potentially pathogenic bacteria involved in acute lower respiratory tract infections, which constitute one of the main causes of morbidity and mortality among children younger than six years of age, particularly in developing countries. In order to determine the percentage of carriers of these microorganisms, 200 nasal and pharyngeal swabs obtained from children that attended four pre-school institutions in Zulia State during the school year 2000-2001, were processed. Isolation and bacterial identification were made following the conventional methodology. The carrier percentage identified was 73,50%, of which 48,98% presented nasal colonization; 10,20% pharyngeal colonization and 40,82%, carried these bacteria in both nose and pharynx. S. aureus was colonizing the frontal nasal passages in 49,50% of the children studied. Around 12,00% of the pre-school children were found to be nasal carriers of H. influenzae, and 13,50% carried this same pathogen in the pharynx. Oropharyngeal colonization by beta-hemolytic streptococci was detected in 27,00% of the children, distributed in the following manner: 8,00% of group A; 12,50% group B; 1,50% group C; 4,00% group G and 1,00% was ungrouped. For S. pneumoniae, 10,50% of nasal and 3,00% of pharyngeal carriers were identified. Only 1,50% of the children studied carried N. meningitidis. Carriers of B. catarrhalis were not found. The differences obtained in the percentage of carriers according to the age and sex were statistically not significant. Resumen: Frecuentemente, la nasofaringe es colonizada por bacterias potencialmente patógenas involucradas en infecciones agudas del tracto respiratorio inferior, las cuales constituyen una de las principales causas de morbi-mortalidad entre los niños menores de seis años de edad, particularmente en países en desarrollo. Para determinar el porcentaje de portadores de estos microorganismos, se procesaron 200 exudados nasales y faríngeos provenientes de niños que asistían a cuatro instituciones pre-escolares del Estado Zulia, durante el año escolar 2000-2001. El aislamiento e identificación bacteriana se hizo siguiendo la metodología convencional. Se obtuvo 73,50% de portadores, de los cuales 48,98% presentaban colonización nasal; 10,20% colonización faríngea y 40,82%, portaban estas bacterias, tanto en nariz como en faringe. S. aureus se encontró colonizando las fosas nasales anteriores en el 49,50% de los niños estudiados. 12,00% de los pre-escolares, resultó portador nasal de H. influenzae y 13,50%, portaba este probable patógeno en faringe. Se detectó colonización orofaríngea por estreptococos beta-hemolíticos en 27,00% de los niños, distribuidos de la siguiente manera: 8,00% del grupo A; 12,50% grupo B; 1,50% grupo C; 4,00% grupo G y 1,00%, resultó no agrupable. Para S. pneumoniae, se obtuvo un 10,50% de portadores nasales y 3,00% de portadores faríngeos. Sólo 1,50% de los niños estudiados, resultó portador de N. meningitidis. No se encontraron portadores de B. catharralis. Las diferencias obtenidas en el porcentaje de portadores de acuerdo a la edad y sexo, resultaron estadísticamente no significativas.